Psychological Intervention to Improve Communication and Patient Safety in Obstetrics: Examination of the Health Action Process Approach - Derksen, Christina; Kötting, Lukas; Keller, Franziska Maria; Schmiedhofer, Martina; Lippke, Sonia (Frontiers in Psychology, 2022)
Background. Human failure and a lack of effective communication are the main reasons for preventable adverse events, compromising patient safety in obstetrics. To improve safety, team and communication interventions have been implemented but lack feasibility in obstetric care. Psychological models such as the health action process approach might help to improve healthcare workers’ education. Methods. In a cross-sectional online survey with N=129 healthcare workers (study 1) and a paper-pencil survey with N=137 obstetric healthcare workers at two university hospitals (study 2), associations of social-cognitive variables were tested in a path analysis and a multiple regression. Preliminary results informed a communication training for all obstetric healthcare workers. A repeated-measures MANOVA was used to compare pre- and post-intervention data. Results. Social-cognitive variables were associated according to model suggestions (β = -.26 to .45, p < .05) except for planning in the first study. Triggers of adverse events were associated (β = -.26 to .24, p < .05) with communication behavior (study 2), action self-efficacy and planning (study 1), as well as barriers to effective communication (both studies). The intervention was rated positively (M=3.3/4). Afterwards, fewer triggers were reported and coping self-efficacy increased. There were group differences regarding hospital, experience, and time. Discussion. The health action process approach was applicable to safe communication in obstetrics and can be used to inform interventions. A theory-based, short training was feasible and acceptable. Perceived patient safety improved but communication behavior did not. Future research should aim to test a more comprehensive (digital) psychological communication intervention in a thorough RCT design.